2004
DOI: 10.1191/0969733004ne681oa
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Nurses’ Views on End-of-Life Discussions and a Comparison with Physicians’ Views

Abstract: This study investigated Finnish nurses' experiences and views on end-of-life decision making and compared them with physicians' views. For this purpose, a questionnaire was sent to 800 nurses, of which 51% responded. Most of the nurses had a positive attitude towards and respect for living wills, more often than physicians. Most also believed that a will had an effect on decision making. Almost all of the nurses considered it their responsibility to talk to physicians about respecting living wills. Do-not-resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 25 publications
6
68
0
Order By: Relevance
“…Further evidence shows that nurses may have a different approach to CPR and DNACPR from physicians 14 and may place more power with the patient and relatives. 71 One study 70 reported that nurses felt that decisions were often made by medical staff in the patients' best interest but another 63 found that 80% of nurses felt that the patient's view should be the decisive factor. Nurses felt that they should be part of the decision-making process.…”
Section: Key Decision-makersmentioning
confidence: 99%
See 4 more Smart Citations
“…Further evidence shows that nurses may have a different approach to CPR and DNACPR from physicians 14 and may place more power with the patient and relatives. 71 One study 70 reported that nurses felt that decisions were often made by medical staff in the patients' best interest but another 63 found that 80% of nurses felt that the patient's view should be the decisive factor. Nurses felt that they should be part of the decision-making process.…”
Section: Key Decision-makersmentioning
confidence: 99%
“…63,82 Several studies reported that the nurse may be the first person who broaches the subject of a DNACPR order with the patient, after developing a rapport with them, 14 and they are consulted by the physician about DNACPR status 38,63,67,69,89 and may follow up the physician's discussion to check their understanding. 68 Generally, nurses felt that the overall responsibility should lie with the medical consultant or treating physician 14,63,70 but specialist registrars in one English study 93 had differed in their opinion from that of their consultant at some point (n = 126/235, 54%), with many (n = 198/235, 84%) feeling that the decision should not lie solely with the consultant. Further evidence shows that nurses may have a different approach to CPR and DNACPR from physicians 14 and may place more power with the patient and relatives.…”
Section: Key Decision-makersmentioning
confidence: 99%
See 3 more Smart Citations